Judaism and its social metaphors: Israel in the history of Jewish thought - Neusner, Jacob (Cambridge University Press, 1989)
The crisis in Palestine is a manifestation of Israel's historical significance to the Jewish people. Jacob Neusner examines the crucial role of the definition of Israel in the history of Judaic thought. He argues that Judaic sages have constructed various metaphoric images of Israel - as family, as chosen people, as a nation - in order to express changing theological concerns as the religion evolved. The history of the definition of Israel is revealed as the reflection of the history of Judaism itself. This is a bold and original interpretation of the way in which Jews, as well as other peoples, define themselves.